Walking towards educational improvement: Reflection and análisis in the self-assessment in Castilla-La Mancha centers - Mora Alonso, Margarita; Moratalla Isasi, Silvia (Avances en Supervisión Educativa, 2023)
The evaluation of educational centers in Castilla-La Mancha responds to the need to know the quality of their response and allows to provide to the educational Administration sufficient, objective and relevant information on educational processes and results to make the necessary readjustments in educational centers to improve the quality of the system in general of this region. For this reason, since 2003 the areas and dimensions that must be evaluated both internally and externally in educational centers have been established. Currently, the evaluation model has been updated, making it a more flexible and less bureaucratic evaluation process. The external evaluation is an habitual action in the education inspectors that has the purpose of helping to obtain a greater knowledge of the educational reality centers and obtaining relevant conclusions for the educational system evaluation in Castilla-La Mancha.
Keywords: assessment of centers; improvement plan; self assessment; education inspection